Perspektif Psikologi Keluarga (Kajian Tentang Wujud Cinta Kasih Orang Tua di Dusun Blokagung Desa Karangdoro Kecamatan Tegalsari Kabupaten Banyuwangi) - Sugiyono Sugiyono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
This research is focused on "The Realization of the Love of Parents in Blokagung Hamlet, Tegalsari District, Banyuwangi Regency". This research uses the descriptive method with a case study, that is a description and comprehensive explanation about various aspect of the individual, a group, a program or a social situation. The research used interview technique and participant observation. After the researcher conducted the observation and interview to the parents and children in Blokagung sub-district, Tegalsari Sub-district resulted that the form of behavior pattern of children in Blokagung Hamlet resulted from the touch of physical attention and speech in the family, social and social life. Thus, parental love affects the behavior of children in Blokagung Village, Karangdoro Village, Tegalsari District, Banyuwangi District.